Zinc-Induced Transposition of Insertion Sequence Elements Contributes to Increased Adaptability of Cupriavidus metallidurans - Vandecraen, Joachim; Monsieurs, Pieter; Mergeay, Max; Leys, Natalie; Aertsen, Abram; Van Houdt, Rob (Frontiers in Microbiology, 2016)
Bacteria can respond to adverse environments by increasing their genomic variability and subsequently facilitating adaptive evolution. To demonstrate this, the contribution of Insertion Sequence (IS) elements to the genetic adaptation of Cupriavidus metallidurans AE126 to toxic zinc concentrations was determined. This derivative of type strain CH34, devoid of its main zinc resistance determinant, is still able to increase its zinc resistance level. Specifically, upon plating on toxic zinc medium, resistant variants arose in which a compromised cnrYX regulatory locus caused derepression of CnrH sigma factor activity and concomitant induction of the corresponding RND-driven cnrCBA efflux system. Late-occurring zinc resistant variants likely arose in response to the selective conditions, as they were enriched in cnrYX disruptions caused by specific IS elements whose transposase expression was found to be zinc-responsive. Interestingly, deletion of cnrH, and consequently CnrH-dependent adaptation potential, still enabled adaptation by transposition of IS elements (ISRme5 and IS1086) that provided outward-directed promoters driving cnrCBAT transcription. Finally, adaptation to zinc by IS reshuffling can also enhance the adaptation to subsequent environmental challenges. Thus, transposition of IS elements can be induced by stress conditions and play a multifaceted, pivotal role in the adaptation to these and subsequent stress conditions.